Socio-economic implication of women in international migration - Tatyana Lipai (Revista română de economie, 2017)
Industrial, economic, scientific and cultural development was spread over the whole country, including distant rural areas. Self-contained, independent Soviet economy called for a differentiation in industry and education. To provide for the new demands new educational establishments were being built, new specialists in various fields of industry and science were being prepared. Women were encouraged to work in the system of science and higher education. The greatest influx of women to Russian science occurred soon after World War II. The formation of a new, self-conscious female personality was under way. The Soviet state was in need of women?s hands and wits to realize the economic modernization. At the same time, the Soviet power could not free the women-scientists from the household responsibilities and delegate these functions to the state.
2665773-9; 2344-4657; Revista română de economie; 717197875